Nexus between FDI and globalization-led energy diversification in BRICS: Fresh evidence from a newly constructed Energy diversification index - Md Qamruzzaman (Energy Strategy Reviews, 2022)
The motivation of the study is to gauge the role of foreign direct investment and globalization on energy diversification in BRICS (Brazil, Russia, India, China and South Africa) for the period 1985–2019 by utilizing a newly constructed energy diversification index. The study performed several econometrical tools such as both conventional and structural break unit root tests, long-run co-integration between variables investigative by performing the novel combined co-integration test, augmented autoregressive distributed lagged (AARDL) implemented for exploring long-run co-integration and explanatory variables coefficients on energy diversification both in the long-run and short-run and directional causality performed with Fourier TY causality test. Stationary tests established variables are integrated in mixed order, suggesting variables become stationary at a level or after the first difference but neither for the second difference. Combined co-integration and the AARDL test ascertained the long-run association in the empirical equation. Refers to long-run coefficients of FDI and GLO, it revealed a positive and statistically significant linkage with energy diversification. In addition, the causality test reveals directional effects between FDI, GLO and energy diversification index, but the direction differs from among economics. Furthermore, the study performed a robustness test by implementing dynamic OLS, fully modified OLS and CC regression. It is found to the sign of long-run coefficients, especially FDI and GLO, as in the same line of robust tests. On policy grounds, it is undoubtedly established that to ensure energy sustainability through energy source diversifications, the critical role of FDI and globalization have to grab with a serious note in BRICS nations.